1964
DOI: 10.1007/bf00177954
|View full text |Cite
|
Sign up to set email alerts
|

Origin, age, and composition of meteorites

Abstract: There are perhaps as many opinions as to the origin of meteorites as there are students of meteorites. Probably in no other branch of natural science is there such a wealth of observational data coupled with such a lack of unanimity in interpretation." (WooD, 1963a) Abstract. This paper attempts to bring together and evaluate all significant evidence on the origin of meteorites.The iron meteorites seem to have formed at low pressures. Laboratory evidence shows that the absence of a Widmanst~itten pattern in me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
170
1
1

Year Published

1972
1972
2012
2012

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 657 publications
(181 citation statements)
references
References 150 publications
9
170
1
1
Order By: Relevance
“…In fact, there is strong evidence, both chemical (Anders, 1964) and orbital (Anders, 1971) that most meteorites are derived from a small number (probably less than a dozen) of parent bodies. An interesting possibility is that some of the Apollo asteroids, such as…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In fact, there is strong evidence, both chemical (Anders, 1964) and orbital (Anders, 1971) that most meteorites are derived from a small number (probably less than a dozen) of parent bodies. An interesting possibility is that some of the Apollo asteroids, such as…”
Section: Discussionmentioning
confidence: 99%
“…Because there are many indirect arguments (Anders, 1964) which indicate that most meteorites are fragments of asteroid bodies, and since McCord, et al (1970) 'have successfully identified the spectral reflectance curve of one asteroid, Vesta, with that of a basaltic achondrite, laboratory measurments on meteorite samples should prove useful in an intrepretation of asteroid surfaces. We 'have chosen to study the spectral, photometric, and polarimetric properties of the Bruderheim olivine-hypersthene chondrite, which is representative of the most common meteoritic material recovered on Earth (Mason, 1962), and, hence, might also be the most common in interplanetary space.…”
Section: Introductionmentioning
confidence: 99%
“…The major uncertainty in evaluating any particular asteroidal object as a source of some portion of the terrestrial meteorite flux lies in the incomplete understanding of the mechanism which converts the original orbit into one which intersects that of the earth. A variety of mechanisms have been proposed including close encounters with Mars (Anders, 1964;Arnold, 1965), secular perturbation (Kozai, 1962;Williams, 1969), resonant perturbations (Zimmerman and Wetherill, 1973), secular resonant accelerations (Williams, 1973) and non-gravitational accelerations (Peterson, 1976). Several authors predict that specific asteroids should be providing a significant contribution to the terrestrial flux if their mechanism is dominant.…”
Section: Additional Information Sourcesmentioning
confidence: 99%
“…Anders 1964;Keil 1964;Heymann 1967;Neal et al 1981;Walsh & Lipschutz 1982;Walsh et al 1983;Friedrich et al 2001Friedrich et al , 2002Friedrich et al , 2008Grier et al 2004;Horz et al 2005;Friedrich 2006;Ferroir et al 2008;Hirata et al 2009). Consequently, prior to a chemical study, it is convenient to determine whether the chondrite has been affected by shock, and to what extent.…”
Section: Introductionmentioning
confidence: 99%